2014
DOI: 10.12691/ajbr-2-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Prevalence of Hepatitis B and Hepatitis C Virue Co-Infection among Pregnant Women in Nigeria

Abstract: This study was carried out to determine sero-prevalence of hepatitis B and hepatitis C virus co-infection among pregnant women. Viral hepatitis during pregnancy is associated with high risk of maternal complications; infections with Hepatitis B virus (HBV) or the Hepatitis C virus (HCV) are public health problems. Worldwide, there are about 350 million HBV carriers and 130 to 170 million people infected with HCV. The presence of HBV and HCV was determined using third-generation enzyme immunoassay (EIA), reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
51
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 51 publications
15
51
3
Order By: Relevance
“…The very high prevalence among children may suggest vertical as well horizontal transmission especially as the virus is not vaccine preventable. Similar to our observation, some researchers have reported highest infection rates among those aged 21 -40 years [15,20,21] and 26 -35 years [10]. The high prevalence rates found among young adults maybe partly be a reflection of cumulative risk exposure to the virus with age.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The very high prevalence among children may suggest vertical as well horizontal transmission especially as the virus is not vaccine preventable. Similar to our observation, some researchers have reported highest infection rates among those aged 21 -40 years [15,20,21] and 26 -35 years [10]. The high prevalence rates found among young adults maybe partly be a reflection of cumulative risk exposure to the virus with age.…”
Section: Discussionsupporting
confidence: 90%
“…This is much higher than the 3.6 -5.0% as estimated for Nigeria by a meta-analysis [10]. Interestingly, Socioeconomic status has been noted as a good indicator of low awareness of viral disease transmission [24].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These research outcomes were slightly higher than HBV seroprevalence reported by Tuba and his co-researchers [31] and Gabor et al [32] who reported 5% among Turkish critically ill emergency patients and those from emergency department of Johns Hopkins University respectively. Anti-HCV seroprevalence among emergency patients reported in this study is more than eleven times that reported by Esan et al [25] among pregnant women attending the antenatal clinic of this same institution. Esan and his colleagues reported 0.15% among pregnant women while the finding among emergency patients was 1.74%.…”
Section: Discussionsupporting
confidence: 53%
“…The estimated global prevalence of HBV/HCV dual infection is approximately 5%-20% in HBsAg positive patients and 2%-10% in HCV positive patients, with a quite different geographical distribution, as reviewed by Caccamo et al [24]. Esan et al reported a prevalence of 0.15% among pregnant women in southwest Nigeria [25].…”
Section: Introductionmentioning
confidence: 99%